A novel dermal delivery system using natural spicules for cosmetics and therapeutics. (1st February 2022) - Kim, Tae Gon; Lee, Yoonjin; Kim, Min Seo; Lim, Jaehong
Abstract: Background: Dermal delivery is versatile in therapeutics as well as cosmetics in pursuit of enhancing safety/efficacy and alleviating pain/fear to alternate oral/injective administrations. Natural siliceous spicules offer a potential approach via simple topical medications to circumvent poor penetrations through the skin barrier by loading, carrying, and releasing the active ingredients in a highly efficient and controlled manner. Aims: The delivery of ingredients loaded on spicules is assessed to improve the dermal efficacy compared to simple topical treatments. Methods: First, needle‐like spicules were isolated from natural freshwater sponges. Then, the active ingredient was loaded via liposome formations. Finally, the dermal efficiency was evaluated. Results: Natural siliceous spicules were purified, sorted, and fully characterized to appear 250 μm of length and 12 μm of diameter on average. A model ingredient, pectolinarin, was efficiently loaded onto the internal space of spicules via lecithin‐based liposome formations. The penetration was visualized using a porcine skin sample with a fluorescent dye and assessed quantitatively by a Franz diffusion cell system. Dermal absorption rate was measured 73.4%, while the percutaneous penetration rate was 2.2%. The release pattern turned out a simple diffusion analyzed by Fick's law and Higuchi model. The liposomes loaded onto spicules were further stabilized by a hydrophobic capsulation, which may benefit the overall efficacy of the ingredient. Conclusion: A novel dermal delivery system is beneficial to improve the topical efficacy of biologically active ingredients. The outcomes shed a light upon developing skin‐protective/improving cosmetics and therapeutics with enhanced performance.